SOCIETY ACTION RESEARCH SEBAGAI PILAR TRANSFORMASI PERTANIAN ORGANIK BERBASIS KOMUNITAS DALAM MENGHADAPI KRISIS IKLIM YANG BERKELANJUTAN - Bagus Indrawan; Irfan Gutawa; Muhammad Khusain Muslimin (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
The climate crisis presents an existential challenge to food security and the sustainability of the agricultural sector. Conventional agriculture is often part of the problem, contributing to greenhouse gas emissions and environmental degradation. In response, the transformation to community-based organic farming has emerged as a vital, adaptive, low-emission solution. However, this transition is complex and requires approaches that are not only technical, but also social and participatory. This article examines the central role of Society Action Research (SAR) as a methodological pillar in facilitating this transformation. SAR is positioned as a participatory approach that empowers farming communities as active subjects—not objects—in the change process. Through a dialogic cycle encompassing problem identification, planning, action, and collective reflection, SAR enables farmers to collaboratively develop locally relevant, innovative solutions for organic farming. This process simultaneously builds adaptive capacity, strengthens social cohesion, and enhances community self-reliance. This study argues that SAR is a crucial instrument for ensuring that the transformation to organic farming is not only technically successful but also socially grounded, equitable, and sustainable, thus building effective community resilience in the face of the climate crisis